Using pharmacokinetics for tailoring prophylaxis in people with hemophilia switching between clotting factor products: A scoping review. Issue 3 (20th May 2019) - Yu, Jacky K.; Iorio, Alfonso; Edginton, Andrea N.; ,
Abstract: The objective of this scoping review is to summarize the current use of pharmacokinetics for tailoring prophylaxis in hemophilia patients switching between clotting factor products. Patients with hemophilia may require switching of clotting factor concentrates due to a variety of factors, but there have been perceived risks associated with switching, such as inhibitor development or suboptimal protection due to inadequate dosing while titrating treatment. Studies that look at patients switching from one clotting factor concentrate to another are categorized in terms of their primary and/or secondary objectives, notably biosimilarity and comparative pharmacokinetic studies and inhibitor development studies. Research on how best to switch concentrates with respect to dosing regimen are lacking, and currently a trial‐and‐error approach is used for dosing the new factor concentrate. In the future, studies looking at the predictability of pharmacokinetics (PK) of a new factor concentrate based on individual PK knowledge of the original factor concentrate may offer clinical benefit by providing a safer switching approach and protocol.